A New Coast Strategies for Responding to Devastating Storms and Rising Seas - Peterson, Jeffrey (Island Press/Center for Resource Economics : Imprint: Island Press, 2019)
"This is a timely book... [It] should be mandatory reading for all persons seeking election to high public office. Followed by a test, with posted grades." Minnesota Star Tribune "A New Coast is a compelling assessment of the dramatic changes that are coming to America's coast. Peterson offers insights and strategies for policymakers, planners, and business leaders preparing for the intensifying impacts of climate change along the coast." Midwest Book Review "Communities along the American coast face hard choices on how to deal with storms and rising seas. A New Coast will help them manage these risks as well as guide the federal government in supporting this important effort. George J. Mitchell, former U.S. Senator from Maine and former U.S. Senate Majority Leader "Risks to our coasts from storms and rising seas have been known for decades, but efforts to prepare for these threats have been limited. A New Coast offers a timely and thoughtful framework for governments, businesses, and organizations to work together to meet these challenges. Peterson tackles the difficult challenge of linking science and experience from devastating storms with forward-thinking public policy and exhorts us to choose leadership over crisis management. William D. Ruckelshaus, former Administrator of the Environmental Protection Agency "This unbelievably comprehensive and well-researched book covers everything from the drivers of sea level rise and the range of its impacts to existing programs and solutions-and concludes with arguments for a new national program to prepare for more severe storms and rising seas. This book is a must-read for coastal management planning and for action at multiple scales. Kathy Jacobs, University of Arizona; Director, Third National Climate Assessment "A New Coast is timely and a very important look at the policy challengesposed by ever-rising sea level in addition to increased flooding from extreme weather events. It is thorough, well researched, up-to-date, and thought provoking. Jeff Peterson is very familiar with U.S. policy on the topic and qualified to propose big change, which he does, unflinchingly. John Englander, oceanographer and author of High Tide on Main Street "Enlightening. Traditional interpretations of 'coastal flooding' are being superseded quickly by the realities of storms and sea level rise. Peterson offers an incredibly thoughtful blueprint for federal leadership to manage these unprecedented changes to our nation's coastline. His remedies are daunting, yet practical and hopeful. One can only hope that future presidents, governors, mayors, and business leaders will heed his call to action. The economic, ecological, and cultural health of our coastal communities is at stake. J. Charles Fox, former Secretary, Maryland Department of Natural Resources; Assistant Administrator, U.S. Environmental Protection Agency "This important and comprehensive book is a must-read for coastal policymakers who are grappling with impacts from rising seas and more intense storms. It captures not only the challenges communities are facing due to climate change, but also useful examples and policy recommendations for advancing adaptation efforts at all levels of government. Jessica Grannis, Adaptation Program Director, Georgetown Climate Center.